Hemoadsorption as part of a multimodal therapy concept to treat Capnocytophaga sepsis with thrombocytopenia and multiple organ failure. Issue 1 (January 2023) - Kreutz, Julian; Choukeir, Maryana; Chatzis, Georgios; Schieffer, Bernhard; Markus, Birgit
Background: Capnocytophaga, a bacteria native to the oral flora of canines, in rare cases can lead to severe infections resulting in septic shock, respiratory tract infection, and multiple organ failure. In case of trauma following animal bites with rapidly progressing clinical courses, also adjunctive therapeutic measures such as extracorporeal blood purification therapies might be beneficial. Case presentation: We report on a 68-year-old male who was hospitalized with fever, oliguria and repeated vomiting after suffering a minor bite by his dog. On admission, he was diagnosed with sepsis. In addition, his coagulation status was markedly deranged resulting in the administration of mass transfusions to stabilize his coagulative status. Following detection of Capnocytophaga canimorsus, anti-infective therapy was initiated. In the context of a progressive respiratory deterioration and an increasing vigilance disorder, he had to be intubated. Due to development of renal failure, dialysis was started in conjunction with CytoSorb hemoadsorption therapy to control the hyperinflammatory condition. All of the applied therapeutic measures led to a rapid clinical stabilization, a control of the hyperinflammatory situation, and an improvement in his neurological status. The therapy was well tolerated with no complications encountered. Conclusions: This case supports the clinical recognition of severe Capnocytophaga infection that can lead to critical conditions even in immunocompetent patients. Combined broad spectrum antibiotic therapy, mass transfusions, CRRT, and CytoSorb hemoadsorption therapy resulted in a control of the critical situation. However, further research is needed to fully elucidate the role of hemoadsorption in this rare but life-threatening setting.